Sm0.5Sr0.5CoO3-δ - Ce0.9Sm0.1O1.95 nanocomposites for reversible electrochemical cells. - Dos-Santos-Gómez, Lucía; Zamudio-García, Javier; Caizán-Juanarena, Leire; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (My University, 2023)
The generation of electricity through environmentally friendly sources of energy has been one of the main challenges of our society in the last decades. Nevertheless, the irregular and seasonal disposition of renewable energy requires devices for energy storage and conversion. Reversible electrochemical cells can address this approach by operating as an electrolyser, when an excess of electricity is available, and as a fuel cell, when the electricity is needed afterwards [1]. The efficiency of air electrodes with poor ionic conductivity may be improved by adding a second phase with high ionic conductivity, i.e. CeO2 and Bi2O3-based electrolytes. Many studies have shown that composite electrodes have higher efficiency than the single-phase ones due to the increased active area [2]. Traditionally, composite electrodes are prepared by mechanically mixing the pristine materials but, unfortunately, it is difficult to control the composition distribution with this method. In this work, Sm0.5Sr0.5CoO3-δ-Ce0.9Sm0.1O1.95 (SSC-CSO) nanocomposite cathodes are successfully prepared in a single process by using the freeze-drying precursor method, in a single-step synthesis, from a precursor solution containing all cations in stoichiometric amounts. SSC and CSO are formed simultaneously, reducing the preparation time, which is an important improvement for industrial application. Different percentages of SSC-CSO are investigated: 100-SSC, 80-SSC, 60-SSC and 50-SSC. The electrode is composed of nanometric particles, providing high active area for the electrochemical reactions. The CGO addition suppresses the grain growth of the nanocomposite cathodes, rendering lower particle size, from 0.53 to 0.32 nm of diameter for 100-SSC to 50-SSC, respectively. This is explained by the presence of CGO as secondary phase, which limits the cation diffusion and the grain growth rate. A low polarization resistance of 0.088 Ω cm2 is obtained at 700 °C for 50-SSC.
Keywords: Materiales nanocompuestos; Electroquímica - Aparatos e instrumentos; Pilas de combustible; Nanocomposites; Reversible electrochemical cells; Energy